Charleso Dickenso kūrybos recepcija Lietuvoje: vertimų tradicija ir praktika (I dalis) - Rudaitytė, Regina (Literatūra, 2010)
Charles Dickens has been recognized in Lithuania as a world-famous canonical English writer, the most emblematic representative of the Victorian Age. For ordinary and less versed readers his books have been usually associated with the rainy and foggy England, the soot, smog and squalor of London, the plight of the poor and the disinherited, with Christmas sentimentality, charity and philanthropy. For many decades in the popular Lithuanian imagination his name alone has been a label, a trade-mark which has stood for everything that is English. Many of his works (albeit not all) have been translated into Lithuanian; some of them were printed in several editions and had a wide circulation. On the other hand, however, Dickens’s writing enjoyed a belated discovery and reception in Lithuania if compared with other European countries. It is only after his death that the first and very modest (both in volume and quality) translations of his works started appearing. This was determined, first of all, by a set of historical, political and cultural circumstances as well as specific literary tastes and national literary traditions which prevailed in Lithuania in the nineteenth and twentieth centuries and which further shaped a specific reception of English literature in general and of Dickens’s art in particular. The beginning of the reception of Dickensian writing in Lithuania is traced back only to late nineteenth century.The specific Lithuanian response to Dickens’s writing might be defined as shifting from one extreme to the other: enthusiastic reception in the inter-war years and particularly in the period of Soviet occupation, and declining interest and popularity today. In view of the peculiar character of the response, the article discusses the Lithuanian reception of Dickens focusing on Lithuanian translations of his works which is a very significant factor in the reception. An impressive scope of Lithuanian translations in multiple editions testifies to the significance and popularity of the great English novelist’s writing among the readers, publishers and critics.